3X^2y-{xyz-(2xyz-9x^2z+4x^2z)+[3x^2y+(4xyz-5x^2z-3xyz)]}=3x^2y-xyz+2xyz-9x^2z+4x^2z+3x^2y+4xyz-5x^2z-3xyz=3x^2y+3x^2y-xyz+2xyz+4xyz-3xyz-9x^2z+4x^2z-5x^2z=6x^2y+2xyz-10x^2z
化简3X^2y-{xyz-(2xyz-9x^2z+4x^2z)+[3x^2y+(4xyz-5x^2z-3xyz)]}等于
1个回答
相关问题
-
3x^2y-{xyz-(2xyz-x^2z)-4x^2z+[3x^2y-(4xyz-5x^z-3xyz)]}
-
先化简,再求值:3xyz+2(x²y+y²z-xyz)-xyz+2z²x,其中x=1、y=-1、z=2;
-
3x²y-[2x²y-(2xyz-x²z)-4x²z]-xyz,其中x=-2 y
-
3x^2y-[2x^2y-(2xyz-x^2z)-4x^2z]-xyz ,其中x=-2,y=-3,z=1
-
(x-y)^4*(y-x)^3*(x-y)=?--------- (2xyz^2)^2*(-xy^2z)-(-xyz)^
-
X^2Y-[-X^2Y+(XYZ-X^2Z)+XYZ]-X^2Z,其中x=-1,y=-2,z=1/3
-
已知A=2x3-xyz,B=y3-z2+xyz,C=-x2+2y2-xyz,且(x+1)2+|y-1|+|z|=0.
-
已知xyz满足|3x-2y+z|+|2x+y+2z|=0(xyz不等于o)求x+y除以z
-
x^2(y+z)+y^2(z+x)+z^2(x+y)-(x^3+y^3+z^3)-2xyz
-
因式分解:x3+x2z+xyz+y2z-y3